Prevalence of Specific Low Back Pain in A Sindh Rural Population - Muhammad Saleh Khaskheli, Rafia Tabbasurn, Munazzah Meraj, Rao Irfan, Aijaz Hussain Awan, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the prevalence of specific Low Back Pain (LBP) in rural population of Sindh. Methods: This cross- sectional study on the prevalence of specific Low Back Pain (LBP) in the rural setting of Shaheed Benazirabad during five years in population aged 14 years to 70 years. Sample was recruited from the total number of patients during last five years who visited at Pain Center Peoples Medical Hospital Nawabshah (SBA). Results: Outof 4,568 cases of LBP, 2,642 (57.84%) were females. The mean age was 40±15.98 in male and 35.14+17.19 years in females. Prevalence of LBP was consistently higher in females (57.84%) than in males (42.16%) in all age groups.Nonspecific low back painwas detected in 3838 (84%) cases, and 2,279 (59.4%) were female; while specific LBP was detected in 730 (16%) patients with male 363 cases (49.43%) Specific LBP diagnoses were herniated nuclei pulposi (30.14%), osteoporosis (20.65%), sprain/strain (11.09%), sacroiliaitis (10.14%), intervertebral disc degeneration (8.910. ), facet arthropathy (7.94%), inflammation (6.97%), infection (2.88%). Four cases of ankylosing spondylitis were also detected and fracture (0.41%). Herniated nuclei pulposi (N=220) was top ranking disorder. Conclusion: Prevalence of specific low back pain in Sindh rural population in females was consistently higher than in males in all age groups. Early intervention is recommended in serious condition to reduce the burden.